Acute respiratory failure due to thyroid storm developing immediately after delivery. Issue 12 (1st November 2015) - Kitazawa, Chie; Aoki, Shigeru; Takahashi, Tsuneo; Hirahara, Fumiki
Key Clinical Message: Acute respiratory failure occurs in less than 0.1% of pregnancies. Thyroid storm should be included in the differential diagnosis of possible causes of acute respiratory failure occurring immediately after delivery, and delivery is a high risk factor for thyroid storm in pregnant women with thyrotoxicosis. Abstract : Acute respiratory failure occurs in less than 0.1% of pregnancies. Thyroid storm should be included in the differential diagnosis of possible causes of acute respiratory failure occurring immediately after delivery, and delivery is a high risk factor for thyroid storm in pregnant women with thyrotoxicosis.